Pendugaan Potensial Penyebaran Mineralisasi Sumberdaya Timah Primer Menggunakan Metode Geomagnetik Pada Wilayah IUP PT TIMAH (Persero) Tbk Di Desa Pengarem Kecamatan Tukak Sadai Kabupaten Bangka Selatan - Teo Aldino; Guskarnali Guskarnali; Irvani Irvani (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2017)
Exploration is a phase before mining activity which is to know, estimate, and attain the measurement, shape, position, average ore content, and also the amount of minerals reserved sediment which are to know economic value. Based on the discovered outcrop, IUP PT TIMAH (Persero) Tbk located in Pengarem Village, Tukak Sadai District, South Bangka it is allegedly has potential source of cassiterite reserved sediment . in case to know the potential zone of source and the spread direction , it is needed to do exploration, one of it is by using geomagnetic method. By using 2 units of magnetometer tool along with base magnetometer application and mobile magnetometer to read (suseptibility) stones magnetic and minerals under the surface. The number of reading lines is 17, distance of the reading point is 10 m, with the number of reading point is 1587, the length of lines is 59 m. Based on the result of reading the geomagnetic method in Pengarem Village with IGRF value is 43204,2 inclination corners -23,493 declination 0,616 which are already corrected by Oasis Montaj V6.4.2 software owns variety value of suseptibility. The highest value is 52,1 nT and the lowest is -36,2 nT. The magnetic anomali contour map that is produced shows that there are potential zone and spread direction of cassiterite source from southwest to northeast. Analysis and conclusion based on geology data.